2007
DOI: 10.1021/bi0621967
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Interactions Are Not Required for Amyloid Fibril Formation by Islet Amyloid Polypeptide but Do Influence the Rate of Fibril Formation and Fibril Morphology

Abstract: Amyloid formation has been implicated in a wide range of human diseases, and a diverse set of proteins is involved. There is considerable interest in elucidating the interactions which lead to amyloid formation and which contribute to amyloid fibril stability. Recent attention has been focused upon the potential role of aromatic-aromatic and aromatic-hydrophobic interactions in amyloid formation by short to midsized polypeptides. Here we examine whether aromatic residues are necessary for amyloid formation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
174
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(182 citation statements)
references
References 39 publications
7
174
0
1
Order By: Relevance
“…Our multimodal analysis of the amyloid peptide aggregates clearly indicates that aromatic residues are not essential for self-assembly. Nevertheless, they alter the kinetics of aggregation as seen previously with the whole amyloid protein (35) and increase the proportion of disordered aggregates. Molecular dynamics simulations show that NL 6 and KE 7 form more disordered aggregates compared with LD 6 and ID 3 in the initial stages.…”
Section: Discussionmentioning
confidence: 64%
“…Our multimodal analysis of the amyloid peptide aggregates clearly indicates that aromatic residues are not essential for self-assembly. Nevertheless, they alter the kinetics of aggregation as seen previously with the whole amyloid protein (35) and increase the proportion of disordered aggregates. Molecular dynamics simulations show that NL 6 and KE 7 form more disordered aggregates compared with LD 6 and ID 3 in the initial stages.…”
Section: Discussionmentioning
confidence: 64%
“…This peptide is not toxic and is a potent inhibitor of amyloid formation and cytotoxicity by wild-type hIAPP (34). Fifth, the 3XL-IAPP peptide is a triple mutant of hIAPP in which the three aromatic residues, F15, F23, and Y37, have been replaced by L (35). It forms amyloid approximately ninefold more slowly than wild-type hIAPP and allows us to test the role of the aromatic residues in membrane disruption.…”
Section: Resultsmentioning
confidence: 99%
“…The triple leucine mutant, 3XL-IAPP, was originally designed to test the role of the aromatic residues in IAPP amyloid formation (35). 3XL-IAPP forms amyloid fibrils with a similar morphology to those derived from wild-type hIAPP, but does so more slowly.…”
Section: Aromatic Residues Are Not Required For Membrane Damage Butmentioning
confidence: 99%
“…We have suggested that, for an essentially unstructured polypeptide chain like hCT, orientation could be driven by a hydrogen bond donor and the center of a benzene ring, which acts as a hydrogen bond acceptor (20,61). The relevance of aromatic residues was postulated (62), predicted theoretically (63), and shown experimentally (64) to increase the rate of fibril formation. Accordingly, intermolecular hydrogen bonds have been reported to play an important role in the association of the hCT molecules (58).…”
Section: Discussionmentioning
confidence: 99%